“METAPHORIZATION IN THE MYTHOLOGICAL LEXICON OF ENGLISH AND AZERBAIJANI LANGUAGES” (COMPARATIVE-HISTORICAL TYPOLOGICAL LINGUISTICS) (Scientific journal of the Fergana State University, 2026)
Metaphors are an important part of language learning and are manifested in the competent study of the language. The expressions included in the composition of mythical metaphors have rich characteristic features. These are features inherent in both the Azerbaijani and English languages. There is a difference here that in English, where there are enough expressions, they are reflected in the dictionaries related to them. In the phraseology of the Azerbaijani language, since these expressions are not selected separately, it is difficult to distinguish them. Thus, Azerbaijani researchers did not separate metaphorical expressions in their scientific works and dictionaries about mythical metaphors, but gave them together with proverbs and sayings. This also makes it relatively difficult to distinguish them from others. Metaphors used in both Azerbaijani and English give a special shade and unique variety to the text during conversation. Metaphors enrich the language, make speech more fluent and attractive. This article discusses the metaphors used in everyday life, their equivalents in the Azerbaijani language. The article explores the use of various innovative teaching approaches and methods when teaching figurative expressions. Innovative methods show the need to study mythical metaphors and idiomatic expressions, thus increasing learners' awareness of unique words, expressions.